Update on hepatitis A vaccination in Argentina (Actualizaciones en Sida e Infectología, 2025)
This issue of ASEI presents an update on the topic prepared by the Vaccine Commission of the Argentine Society of Infectious Diseases (SADI). This update constitutes a fundamental tool for guiding clinical and public health decisions. The document reviews current indications, vaccination schedules, outbreak control strategies, and specificities in immunocompromised hosts.The Editorial Committee of the ASEI Journal encourages all healthcare teams to read, apply, and disseminate this document. Prevention, ultimately, remains the most effective tool for preserving the health of the population.
Keywords: Hepatitis A